PENGARUH POSITIF PARIWISATA TERHADAP KEPUASAN HIDUP DAN NILAI CO CREATION PADA KOMUNITAS DI LINGKAR KEK MANDALIKA - Rinuastuti, Baiq Handayani; Saufi, Akhmad; Asmony, Thatok (Jurnal Magister Manajemen, 2019)
Understanding community behavior related to the impact of tourism as well as the consequences of these impacts is an important matter to be studied in the effort to develop tourism in the future. The purpose of this study is to analyze the positive impact of tourism felt by residents in the Mandalika Special Economic Zone which can affect their life satisfaction and the willingness of the population to create co-creation values with tourists. The results showed that the positive effects of tourism activities and life satisfaction significantly affected the value of Co Creation, but the positive impact of tourism had a not significant effect on life satisfaction. The results of this study are expected to contribute to the development of theory, especially tourism marketing from the perspective of local residents. In addition, it can be used as a basis for consideration of policy makers in the development and marketing of tourism in the Mandalika Special Economic area. Keywords : Positive tourism impacts, life satisfaction, co-creation value, Mandalika SEZ